Acute Toxicity of Hydrogel Polyhexamethylene Guanidine Hydrochloride - S. N. Lebedeva; O. S. Ochirov; M. N. Grigoryeva; S. D. Zhamsaranova; S. A. Stelmakh; D. M. Mognonov (Acta Biomedica Scientifica)
Background. Previously, we have shown that the polyhexamethylene guanidine hydrochloride hydrogel exhibits a pronounced wound healing. At the same time, no studies of the toxic effect of the hydrogel on animals have been conducted. Aim of the research. In the framework of this work, the acute toxicity of the hydrogel polyhexamethylene guanidine hydrochloride was studied in laboratory animals with intragastric administration. Materials and methods. The polyhexamethylene guanidine hydrochloride hydrogel was obtained by crosslinking the amino end groups with formaldehyde. An acute toxicity study was carried out (P 1.2.3156-13, GOST 32644-2014 and the Guidelines for conducting preclinical studies of drugs) in an experiment on outbred mice with a single addition of the test substance in different doses (1000, 3000, 5000, 8000 mg/kg) with fixing indicators (appearance, behavior, condition of the body hair coat, water and food consumption, excretion, body weight and its growth) during 14 days. After the animals were withdrawn from the experiment, autopsy, macroscopic evaluation and weighing of the internal organs were performed. The results showed that with the introduction of the test substance into the animal organism, death during the observation period (14 days) did not occur. It was not possible to determine the semi-lethal dose for the test compound. Conclusion. The conducted studies allow us to conclude that this substance is practically non-toxic and can be classified as hazard class V. Further research will be directed to the formation of hydrogel compositions with medicinal substances.